Differences in treatment response in bronchial epithelial cells from idiopathic pulmonary fibrosis (IPF) patients: a first step towards personalized medicine? - Veith, Carmen; Schneider, Marc; Maas, L.; van der Vliet, A.; van Schooten, F. J.; Kreuter, Michael; Meister, Michael; Boots, A. W.; Kahn, Nicolas (Antioxidants, 2023)
Idiopathic pulmonary fibrosis (IPF) has a detrimental prognosis despite antifibrotic therapies to which individual responses vary. IPF pathology is associated with oxidative stress, inflammation and increased activation of SRC family kinases (SFK). This pilot study evaluates individual responses to pirfenidone, nintedanib and SFK inhibitor saracatinib, markers of redox homeostasis, fibrosis and inflammation, in IPF-derived human bronchial epithelial (HBE) cells. Differentiated HBE cells from patients with and without IPF were analyzed for potential alterations in redox and profibrotic genes and pro-inflammatory cytokine secretion. Additionally, the effects of pirfenidone, nintedanib and saracatinib on these markers were determined. HBE cells were differentiated into a bronchial epithelium containing ciliated epithelial, basal, goblet and club cells. NOX4 expression was increased in IPF-derived HBE cells but differed on an individual level. In patients with higher NOX4 expression, pirfenidone induced antioxidant gene expression. All drugs significantly decreased NOX4 expression. IL-6 (p = 0.09) and IL-8 secretion (p = 0.014) were increased in IPF-derived HBE cells and significantly reduced by saracatinib. Finally, saracatinib significantly decreased TGF-β gene expression. Our results indicate that treatment responsiveness varies between IPF patients in relation to their oxidative and inflammatory status. Interestingly, saracatinib tends to be more effective in IPF than standard antifibrotic drugs.